Education in the Sultanate of Siak: The Study of Manuscripts and Archives of Siak Sri Indra Pura, Riau - Arrafie Abduh; Ellya Roza; Sukma Erni (Lembaga penelitian dan pengabdian kepada Masyarakat, 2021)
This study discusses education in the Sultanate of Siak by studying manuscripts and archives. Manuscripts and archives are the main basis of the information requested about the education needed. The method used is philological and historical research so that the results obtained can be thought of as real education in the imperial era. Research findings on education that get full attention from sulthan are religiously based education. Education is accessed in 3 places ; mosque (surau) domains, schools and ma'had. Education that is carried out in the mosque (surau) about the education of the wider community which includes not only quran learning (reciting), but also usul ul fiqh, tariqat and qasidah (sound art). Education carried out in schools (madrasas) and ma'had also includes learning Qur`an, Islamic law, gramatical, etc. All teachers involved in education must go through the legalization of sultan even though they only teach the Koran (Qur`an). Legalization of becoming a teacher through several processes involving the data collection, qadi to accept eligibility and sultan licensor